Applications of nanomaterials in endometriosis treatment - Yuxue, Jiang; Ran, Sun; Minghui, Fan; Minjia, Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
Endometriosis is a common disease of the reproductive system in women of childbearing age with an unclear pathogenesis. Endometriosis mainly manifests as dysmenorrhea, abdominal pain, and infertility. Currently, medical therapy and surgical treatment are usually used for endometriosis treatment. However, due to the high recurrence rate and many complications, it has greatly affected patients’ quality of life. Nanotechnology is a new technology that mainly investigates the characteristics and applications of nanomaterials. To date, nanotechnology has received widespread attention in the field of biomedicine. Nanomaterials can not only be used as drugs to treat endometriosis directly, but also enhance the therapeutic effect of endometriosis by delivering drugs, siRNA, antibodies, vesicles, etc. This review comprehensively discusses nanomaterial-based therapies for endometriosis treatment, such as nanomaterial-based gene therapy, photothermal therapy, immunotherapy, and magnetic hyperthermia, which provides a theoretical reference for the clinical application of nanotechnology in the treatment of endometriosis.